A comparison of the substance use related risk and protective factor profiles for American Indian and White American youth: a mixed studies review - Nadeau, Melanie; Wise, Kathryn; Sabbella, Revathi B.; Olson, Devon (Frontiers in Public Health, 2024)
Background American Indian youth are disproportionately impacted by substance use compared to White American youth in the United States. This mixed studies review focused on gathering data to examine the similarities and differences between the risk and protective factor profiles for substance use among American Indian and White American youth aged 10-21. Methods A scan of the existing literature was needed to review substance use related risk and protective factors for American Indian and White American youth. Search phrases were created to ensure maximum relevant results from existing literature through 2021. After deduplication, an appraisal tool was utilized to review 343 records. A total of 19 articles were deemed relevant. Data from relevant articles was recorded and categorized into the levels of the Social Ecological Model. Results Significant and salient risk and protective factors of substance use for both American Indian and White American youth presented at the individual, interpersonal (family/non-family), and community levels of the Social Ecological Model. A total of 84 factors were found from relevant articles, 55 risk factors and 29 protective factors. When comparing the American Indian and White American youth profiles, a total of 29 unique differences between American Indian (n = 21) and White American youth (n = 8) were identified. Discussion Results from this review can be utilized to inform Tribal leaders, stakeholders, and policymakers, which will ultimately influence health intervention strategies and prioritizations. Given the limited evidence though, researchers should be responsive to Tribal communities' call to action for utilizing a culturally rooted approach.